2021
DOI: 10.2147/jpr.s304440
|View full text |Cite
|
Sign up to set email alerts
|

The Mediating Role of Pain Catastrophizing on the Association Between Depression and Pain Severity and Interference Among Elderly Asian Immigrants with Chronic Pain

Abstract: The association between depression and chronic pain is well established. However, few studies have examined the pathways from depression to chronic pain. The present cross-cultural study aimed to test the mediating effects of pain catastrophizing on associations between depression and chronic pain (eg, pain severity, pain intensity) among Korean American elderly. Patients and Methods: A total of 132 elderly Korean Americans with chronic pain were recruited from elderly daycare centers and Korean ethnic churche… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
15
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 35 publications
3
15
1
Order By: Relevance
“…Fear-avoidance has been associated with pain in women with chronic pelvic pain and sexual pain (Gatchel et al, 2007;Thomtén et al, 2014). Previous studies have also found that catastrophising mediates the association between depression and pain (Kim et al, 2021;Wood et al, 2013). The mediating role of catastrophising may further explain the mixed findings earlier discussed regarding the association between depression and pain in Endometriosis.…”
Section: Psychological Factors Associated With Painmentioning
confidence: 88%
“…Fear-avoidance has been associated with pain in women with chronic pelvic pain and sexual pain (Gatchel et al, 2007;Thomtén et al, 2014). Previous studies have also found that catastrophising mediates the association between depression and pain (Kim et al, 2021;Wood et al, 2013). The mediating role of catastrophising may further explain the mixed findings earlier discussed regarding the association between depression and pain in Endometriosis.…”
Section: Psychological Factors Associated With Painmentioning
confidence: 88%
“…Further correlation analyses were performed between demographic (i.e., gender, age), clinical characteristics (i.e., months elapsed from injury to assessment) and functional disability to assess suitability for inclusion as potential covariates in further analyses. Rationale for this process was derived from previous analogous research 24 Extending on this empirical rationale, three linear regressions were conducted to establish whether the demographic or clinical variables significantly predicted functional disability outcomes to further justify inclusion as covariates. Preliminary analyses were conducted to check the assumptions of normality, linearity, homoscedasticity, and multicollinearity.…”
Section: Statistical Analysesmentioning
confidence: 99%
“…Results did not support gender, b = -2.55, t(181) = -1.24, p = .216, 95% CI [-6.60, 1.50], β = -.09, R² < 0, age, b = .04, t(178) = 0.52, p = .604, 95% CI [-.10, .18], β = .04, R² < 0, or months to assessment, b = .12, t(169) = 1.22, p = .226, 95% CI [-.07, .31], β = .09, R² < 0, as significant predictors of functional disability outcomes. Based on the findings from both the regression and correlation analyses, and in line with previous research practices, 24 gender, age and months to assessment were not included in further analyses as confounding variables.…”
Section: Analysesmentioning
confidence: 99%
See 1 more Smart Citation
“…30,88 Also, it is important to note that most research did not include individuals with comorbid obesity and, importantly, did not account for the contribution of other significant additional mediators. 26,89,90 Finally, because psychosocial factors tend to be intercorrelated, predictive models in chronic pain should account for this shared variance between predictors to develop parsimonious models of pain and disability. 91 The fact that the present study included three important psychological predictors of disability might explain why not all of them contributed unique variance to physical performance.…”
mentioning
confidence: 99%